Methylene blue chromoendoscopy is more useful in detection of intestinal metaplasia in the stomach than mucosal pit pattern or vessel evaluation and predicts advanced Operative Link on Gastric Intestinal Metaplasia stages - Justyna Wasielica-Berger; Pawel Rogalski; Anna Pryczynicz; Agnieszka Swidnicka-Siergiejko; Andrzej Dabrowski (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Intestinal metaplasia (IM) of the stomach is a precancerous condition that is often not visible during conventional endoscopy. Hence, we evaluated the utility of magnification endoscopy and methylene blue (MB) chromoendoscopy to detect IM. Methods We estimated the percentage of gastric mucosa surface staining with MB, mucosal pit pattern, and vessel visibility and correlated it with the presence of IM and the percentage of metaplastic cells in histology, similar to the Operative Link on Gastric Intestinal Metaplasia (OLGIM) stage. Results IM was found in 25 of 33 (75.8%) patients and in 61 of 135 biopsies (45.2%). IM correlated with positive MB staining (p<0.001) and other than dot pit patterns (p=0.015). MB staining indicated IM with better accuracy than the pit pattern or vessel evaluation (71.7% vs. 60.5% and 49.6%, respectively). At a cut-off point of 16.5% for the MB-stained gastric surface, the sensitivity, specificity, and accuracy of chromoendoscopy in the detection of advanced OLGIM stages were 88.9%, 91.7%, and 90.9%, respectively. The percentage of metaplastic cells detected on histology was the strongest predictor of positive MB staining. Conclusions MB chromoendoscopy can serve as a screening method for detecting advanced OLGIM stages. MB mainly stains IM areas with a high concentration of metaplastic cells.